Logística reversa: um estudo de caso de resíduos eletroeletrônicos em São João do Polêsine - Foletto, Agueda Elisabete Recke (2023)
Abstract: As a result of globalization, innovative technologies are emerging more and more quickly. With the increase in consumption, such technologies end up being quickly included in society's consumption list. Electro-electronic waste is a problem for the government, companies, society and education organizations in their multiple segments, which need to adopt a posture regarding the total cycle of these products visible in the norms expressed by the Associação Brasileira de Normas Técnicas - ABNT. On the other hand, the National Solid Waste Policy (Law 12,305/2010) established that importers, manufacturers, traders and distributors of electrical and electronic items need to implement and structure reverse logistics systems, which aims to return these items later to the consumer for use. them, and the realization of this process must occur separately from the public service of urban cleaning. Proper forwarding of electronic waste after its useful life, through reverse logistics, makes it possible to reduce the amount of inappropriate disposal and increases the promotion of material recovery. With this, we sought to identify the appropriate needs for the treatment of electronic waste, guiding the proper return of these used products and employing the appropriate reuse, destination and recycling.Thus, the objective of this work was to understand how the disposal of electronic waste in the municipality of São João do Polêsine occurs by private organizations. Thus, an interview was applied through a closed questionnaire using the likert scale - multiple choice questions, in order to analyze and identify the needs in dealing with electronic waste in Private Organizations of São João do Polêsine. Considering the factors that were analyzed and the results obtained, it was found that most companies associated with ACISAT (Association of Commerce, Industry, Services, Agriculture and Tourism) in the municipality of São João do Polêsine, do not meet the expectations of the precepts of PNRS. However, there are companies that are still in the process of adapting to the criteria established in Law No. 12,305/2010, having performed some specific actions, but with other actions, considered mandatory, still pending implementation. The general objective of the study was achieved from the construction of the final research product, in the form of a booklet of good practices in the management of electronic waste to be carried out by the companies associated with ACISAT. The purpose of the booklet is to assist in the correct direction of public policies focused on the subject. At the same time, it seeks to encourage further discussions and reflections, aiming at a responsible and sustainable management of electronic waste for all populations.